Improving Financial Literacy Among Students Of Lingga Kencana Vocational School Through Basic Accounting Training - Ardi Bachtiar; Ananda Hadistia; Indri Kharisma (Journal Arbitrase : Economy, Management and Accounting, 2024)
Applying financial literacy is crucial, particularly in the context of the Industrial Revolution 4.0 and Society 5.0. The subject of financial literacy has gained significant traction in scientific circles across several nations, including Indonesia. All people should be able to understand it, as it is one of the fundamental elements of literacy, along with science, digital, literacy, numeracy, and citizenship and culture. In the digital age, financial literacy education is one of the fundamental literacy skills needed to face global life and compete with other nations in fostering wealth (Laila et al., 2019). Both formal education from primary, secondary, and university levels as well as informal education received in the home are crucial in the development of financial literacy (Widayati, 2012). Strong financial knowledge is a prerequisite for sound financial management. According to Said and Amiruddin (2017) and Purniawati and Lutfi (2019), financial literacy affects both family financial management and good financial behaviour. This presentation has shown how important it is to conduct outreach to raise financial literacy, particularly among students at Lingga Kencana Vocational School. Therefore, Pamulang University teachers felt compelled to engage in Community Service (PKM) activities. One of the items they gave to the students they visited focused on enhancing financial literacy by offering fundamental accounting guidance. is to instill in children a sense of the value of financial literacy as a means of preparing them all for the future.